Technology Enhanced Learning in Forensic Medicine: Reforms for the Digital Age (Journal of Forensic Medicine & Toxicology, 2025)
Technology-Enhanced Learning (TEL) is redefining the landscape of medical education, and its integration into Forensic  Medicine marks a significant advancement in how future professionals are trained. This article explores the transforma tive impact of TEL tools on the teaching and learning of Forensic concepts. Challenges, demerits and future directions  are also discussed. By embracing TEL, forensic education becomes more accessible, interactive, and effective, ultimately  preparing learners to meet the evolving challenges of medico-legal practice in a digital age.
Keywords: Technology-Enhanced Learning; Forensic Medicine; Education; Impact